Analysis of the structural and mechanical parameters of the ceramic membranes in the technological process of manufacturing - Pashchenko, Bohdan; Shtern, Michael; Shtefan, Yevgenii; Mikhailov, Oleh (My University, 2016)
The results of complex numerical experiments of this work showed: the distributions of internal porosity of the particles and the amount of accumulated plastic deformation of the base particles on the product volume of the material aren’t uniform; the greatest deformation of the material occurs in the products is in obtuse angles, the lowest — in sharp corners. The patterns of influence of the external forces are similar to known results concerning seals mono dispersed environments.

Результати комплексних чисельних експериментів роботи показали: розподіли внутрішньої пористості частинок і величини накопиченої пластичної деформації частинок основи по об'єму виробу з матеріалу неоднорідні; найбільша деформація матеріалу відбувається у виробах під тупими кутами, найменша - під гострими кутами. Закономірності впливу зовнішніх сил аналогічні відомим результатам щодо ущільнень у монодисперсних середовищ.
Keywords: кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра експертизи харчових продуктів; department of foodstuff expertise; membranes; analysis; the structural and mechanical parameters; аналіз; мембрани; структурно-механічні параметри